Implementasi Program Transformasi Perpustakaan Berbasis Inklusi Sosial Di Perpustakaan Kelurahan Cipayung, Jakarta Timur - Istyarini, Ajeng; Rohmah, Lailatur (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
Library Transformation based on Social Inclusion Program (TPBIS) is one of the national priorities in the 2020–2024 National Medium-Term Development Plan, which aims to improve access and quality of information services, including in urban areas. This research explores the implementation of the TPBIS Program in the Cipayung Village Library, East Jakarta, with the aim of identifying obstacles and efforts to overcome them. The methods used include descriptive qualitative, in-depth interviews, observation, and document study. The research results show that effective communication between policy implementers and stakeholders has resulted in a clear and consistent program understanding. However, there are several obstacles, such as limited human resources, budget authority, and facility requirements. Efforts to overcome these obstacles include assistance by consultants, the appointment of TPBIS Program Administrators/PICs, the implementation of regulations, and advocacy strategies. Further research is needed to develop library budget strategies at the village and sub-district levels to support the sustainability of inclusive libraries.